The Status of Women in Preindustrial Societies. - Whyte, Martin King (Princeton legacy library., 2015)
How does the status of women in different cultures actually compare with that of men? How does this position vary from one realm-religious, political, economic, domestic, or sexual-to another? To examine these questions, Martin King Whyte draws on a cross-cultural sample of 93 preindustrial societies throughout the world. His analysis describes women's roles in historical perspective, offering a much-needed foundation for feminist scholarship as well as provocative thoughts about the future. To determine why women fare better in some societies than others, Professor Whyte compares data from.